2014
DOI: 10.4172/2155-9546.1000299
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effects of Selenium and Alpha-Tocopherol against Lead-Induced Hepatic and Renal Toxicity in Oreochromis Niloticus

Abstract: Lead is a serious poison causing serious injury or death. Current study was designed to investigate the potential protective effect of selenium (Se) and alpha-tocopherol (alpha-toc) against the hepatic and renal toxicity of lead acetate in Oreochromis niloticus. Two hundred and twenty five O. niloticus were divided into five groups; control, lead acetate treated (73.40 mg/liter), Se treated (4 mg sodium selenite/ kg diet), alpha-toc treated (200 mg/kg diet) plus Se + alpha-toc co-treated groups for 10 weeks. L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…9 Different studies showed beneficial renoprotection effects of selenium in lead and cadmium toxicities. 37,38 Plasma glutathione peroxidase produced mainly by kidneys. 24 Selenium can increase glutathione peroxidase production and activity.…”
Section: Renoprotectionmentioning
confidence: 99%
“…9 Different studies showed beneficial renoprotection effects of selenium in lead and cadmium toxicities. 37,38 Plasma glutathione peroxidase produced mainly by kidneys. 24 Selenium can increase glutathione peroxidase production and activity.…”
Section: Renoprotectionmentioning
confidence: 99%
“…The antioxidants compose the group of drugs which has been investigated the most. Selenium and α-tocopherol showed the positive effect for the level of aspartate and alanine transaminases, total protein, urea, creatinine, superoxide dismutase and glutathione, as well as the lipid peroxidation index [33]. Some drugs like morpholine salt of titanic acid with membrane stabilizing and antioxidant properties and sulfur-containing products inproved hepatocytes morphology and biochemical parameters [1].…”
mentioning
confidence: 99%